Bank Efficiency and Determinants of Bank Profitability: Recent Evidence from Vietnamese Banking System, 2006-2013 - Nguyen, Le Van Quynh (2014)
This paper adopts a two-step research design. In the first stage, this study examines the efficiency scores of Vietnamese commercial banks during the period 2006-2013. The paper employs stochastic frontier analysis (SFA) technique with input distance function and one-sided inefficiency u, and suppose that the scale of u depends on some environmental factors z. A “one-step” procedure that specifies the frontier and the way in which z affects u will be estimated by maximum likelihood technique. This procedure is in contrast to a “two-step” model that comprises two separated steps: estimate the stochastic frontier first and then using the regression model to assess the effects of z variables on inefficiency level u. The phase of measuring bank-specific efficiency levels aims to (i) evaluate the economics performance changes of Vietnamese banking system throughout period 2006-2013, and (ii) determine whether there are differences regarding to efficiency levels across different bank categories in terms of size and ownership. It shows that average efficiency score of Vietnamese banking system during 2006-2013 was 64%, and in general, technical efficiency level was on an increasing trend with two peaks at 74% and 86.5% in 2008 and 2011, respectively. No efficiency level difference was found between either bank size groups or bank ownership groups. In the second stage, using panel data estimation with system generalized method of moments (GMM) technique, this paper assesses the impacts of possible bank-specific (including technical efficiency level estimated in the first stage), industry-specific and macroeconomic variables on Vietnamese bank profitability. It is found that the level of capital to assets ratio (EQASS), the liquidity ratio (LODEP), technical efficiency (TE) and GDP Growth (GDPGR) have positive impacts on accounting bank performance (ROA); while concentration ratio (CR4) is negatively related to ROA. Remaining variables, namely impaired loan reserve to gross loan ratio (LORES), market share of individual banks (MS) and unemployment rate (UNEMP) are found to have no effects on bank profitability.